2014
DOI: 10.1186/1556-276x-9-660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photo-assisted electrodeposited on CuInSe2 thin films

Abstract: Photo-assisted one-step electrodeposition has been applied to help in forming smooth and dense CuInSe2 films. The difference in surface morphology and crystalline quality between CuInSe2 films with various photo-assistance has been investigated. In the photo-assisted electrodeposition process, the many kinds of lamps providing maximum light intensity at about 380 to 620 nm were used as light source to be irradiated onto the surface of Mo-coated soda-lime glass substrates. The results suggested effects of photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…(3) With regard to the ternary and quaternary chalcogenides, especially CIGS and CZTS, it is worth further developing the one-step co-deposition method, with the consideration of achieving selenization or sulfurization during the electrodeposition and thus simplifying the manufacturing operations to make the electrodeposition a more competitive technique in delivering low cost solar cells. (4) New ideas, for example, nanoparticle-based electrodeposition [172], photo-assisted electrodeposition [173], in situ monitoring of the deposition [174,175], may create the chances to gain better understanding of the kinetics of electrodeposition, make the control of the composition and microstructure of electrodeposited films more effective, and consequently deliver high quality films. (5) There is generally a lack of theoretical models to simulate the electrodeposition, in particular for the co-deposition of multiple elements.…”
Section: Perspectivementioning
confidence: 99%
“…(3) With regard to the ternary and quaternary chalcogenides, especially CIGS and CZTS, it is worth further developing the one-step co-deposition method, with the consideration of achieving selenization or sulfurization during the electrodeposition and thus simplifying the manufacturing operations to make the electrodeposition a more competitive technique in delivering low cost solar cells. (4) New ideas, for example, nanoparticle-based electrodeposition [172], photo-assisted electrodeposition [173], in situ monitoring of the deposition [174,175], may create the chances to gain better understanding of the kinetics of electrodeposition, make the control of the composition and microstructure of electrodeposited films more effective, and consequently deliver high quality films. (5) There is generally a lack of theoretical models to simulate the electrodeposition, in particular for the co-deposition of multiple elements.…”
Section: Perspectivementioning
confidence: 99%
“…And also these dopants are introduced as substitutional defects on zinc sites. The fact that the radius of 4-coordinate Ga 3+ (0.62 Å) and that of In 3+ (0.81 Å) is closer to that of 4-coordinate Zn 2+ (0.74 Å), make it useful as a codopant for ZnO structures [10,11]. Thin film deposition of ZnO can be carried out by various techniques like sputtering [12], pulsed laser deposition [13], microwave assisted synthesis [14], sol-gel [15], ultrasonic spray pyrolysis [16], chemical bath deposition [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Such extensive investigation enabled the development of annealing maps and radar sketches, which revealed that the postdeposition modifi cation of deposited ZnO-based TCO materials can be the key for developing a replacement for ITO, as it can enhance the electrical properties and stability under environmental conditions by creating oxygen vacancies, [ 26 ] passivation of the grain boundaries, [ 27 ] and other structural improvements [ 28 ] as discussed below.…”
Section: Introductionmentioning
confidence: 99%